Developing an Interactive EFL Digital Vocabulary Book at MAN Palopo Using the 4D Model - Husnaini Husnaini; Wahibah Wahibah; Diva Zahiyah Irfani (Datokarama English Education Journal, 2026)
This study developed a needs-based digital book for English vocabulary and phrases for tenth-grade students at Madrasah Aliyah Negeri Palopo. The study addressed a mismatch between learners' communicative needs and the available English-learning materials. Using a research and development design, the study adapted the 4D model through define, design, develop, and limited dissemination stages. The needs analysis involved 36 students and was supported by classroom observation, interviews, questionnaires, expert validation sheets, and user perception questionnaires. The results showed that students needed practical vocabulary for communication, pronunciation support, visual presentation, translation, and mobile-accessible materials. These findings were translated into a digital book containing thematic vocabulary, common phrase-based expressions, pictures, translations, phonetic guidance, and context-sensitive Islamic and daily-life content. Expert validation indicated that the product was feasible in terms of design, language, and material quality, with scores ranging from 4.00 to 4.42. Student and teacher responses also indicated positive practicality for limited use. The findings should be interpreted as evidence of validity and practicality, not as proof of instructional effectiveness, because no experimental test of learning gains was conducted.